Dilation of Epicardial Coronary Arteries by the G Protein-Coupled Estrogen Receptor Agonists G-1 and ICI 182,780 - Meyer, Matthias R. (S. Karger AG, 2010)
Endogenous estrogens protect from coronary artery disease in premenopausal women, but the mechanisms involved are only partly understood. This study investigated whether activation of the novel G protein-coupled estrogen receptor (GPER, formerly known as GPR30) affects coronary artery tone, and whether this is affected by concomitant blockade of estrogen receptors (ER) α and β. Rings of epicardial porcine coronary arteries suspended in organ chambers were precontracted with prostaglandin F(2)α, and direct effects of G-1 (GPER agonist) and ICI 182,780 (GPER agonist and ERα/ERβ antagonist) were determined. In addition, indirect effects on contractility to endothelin-1 and serotonin (a vasoconstrictor released from aggregating platelets during acute myocardial infarction) were assessed. ICI 182,780 and G-1 caused acute dilation of coronary arteries to a comparable degree (p < 0.05 vs. solvent control). Both GPER agonists attenuated contractions to endothelin-1 (p < 0.05 vs. ethanol), but not to serotonin (n.s.). In summary, these findings provide evidence for direct and indirect coronary artery dilator effects of GPER independent of ERα and ERβ, and are the first demonstration of arterial vasodilation in response to ICI 182,780.